Segara Kerthi Concept as A Source for Developing Educational Games in Pererenan Village - Wiradnyana, I Made; Suwadnyana, I Wayan; Saskara, I Putu Adi (Jayapangus Press, 2025)
The development of educational games has become an increasingly important focus in efforts to improve access and quality of education in various regions, including in rural areas such as Pererenan Village. In this context, the Segara Kerthi concept, which describes the management of the marine environment to maintain sustainability, serves as a valuable source of inspiration. This study aims to explore how the Segara Kerthi concept can be utilized as a foundation for developing an educational game that promotes environmental awareness and supports local values, as well as to analyze the role of the game as a medium of communication. The method used in this research is research and development (R&D) with a media function theory approach. Data were collected through observation, interviews, evaluation, and literature studies. The research resulted in the development of a game titled Segara Watch, which provides an interactive and enjoyable learning experience to introduce knowledge and skills related to marine environmental management and sustainable cleanliness. This game is aligned with the Pererenan Gumi Lestari village motto and supports the vision and mission of the Governor of Bali, I Wayan Koster, Nangun Sat Kerthi Loka Bali.